Research and Practice on the Importance of Diversity and Inclusive Culture in Human Resource Management - Yang Mingyi (SHS Web of Conferences)
In the contemporary era of globalization and social diversity, diversity and inclusive culture have become key aspects of human resource management. This culture promotes the integration of different backgrounds and perspectives, which can effectively enhance employees’ creativity, the company’s innovation capabilities, and market competitiveness. This article explores the importance of diversity and inclusive culture in human resource management and analyzes how to promote and practice this culture in practical work. Firstly, the definitions of diversity and inclusivity and their potential benefits to the enterprise have been determined. Secondly, it analyzed how to embody diversity and inclusivity in employee recruitment, development, and retention. In addition, discussions were held on how to develop this culture through training and leadership, as well as how to improve the overall working environment of the enterprise by establishing and promoting diversity and inclusivity policies. This article emphasizes that the cultivation of diversity and inclusivity is not only a moral requirement but also an important component of corporate strategy, which is crucial for attracting and maintaining global talent and consumers.